Oral Realgar-Indigo Naturalis Formula Plus Retinoic Acid for Acute Promyelocytic Leukemia - Lou, Yinjun; Ma, Yafang; Jin, Jie; Zhu, Honghu (Frontiers in Oncology, 2021)
The treatment paradigm for acute promyelocytic leukemia (APL) is the most remarkable in cancer therapy. The advent of oral arsenic (oral-arsenic trioxide and realgar-indigo naturalis formula [RIF])-based regimens may ensure a therapeutic advance using two oral agents in curing APL. Oral RIF plus all-trans-retinoic acid (ATRA) without chemotherapy is highly effective in patients with APL. The safety profile of RIF plus ATRA makes home-based treatment of APL patients during post-remission therapy possible. To our knowledge, RIF was the first commercially available oral arsenic agent approved in China. RIF plus ATRA regimens are becoming preferred frontline care for APL in China. In this review, we discuss the history and current evidence of RIF-based strategies for treatment of APL. In the near future, an increasing number of APL patients may enjoy a normal quality of life after induction.